FAMILY INTERACTION PATTERN AND CO-DEPENDENCY IN SPOUSES OF ALCOHOL DEPENDENCE IN COMPARISON WITH NORMAL CONTROL - Senthil, M. (International Journal of Research -GRANTHAALAYAH, 2016)
Alcoholism is destructive to those closest to the alcoholic, and it affects families in several different ways. Many times, rehabilitating an alcoholic is only one part of the process of healing a home. Family members may also need support and counseling. Families with alcohol dependent suffer from a range of problems. Spouses can live in constant conflict. The present study aim was to compare the family interaction and codependency in spouses of alcohol dependence in comparison with normal control. It was a cross sectional study and purposive sampling method was used. Sample consisted of 30 spouses of individuals with alcohol dependence and 30 spouses of normal individuals. Alcohol Dependence Questionnaire was administered on the patient and General Health Questionnaire was administered on spouses for screening purpose. Socio-demographic data sheet, Family Interaction Pattern scale, and Co-dependency Scale were administered on the spouse of both groups. The data was analyzed using SPSS.16. The result revealed that spouses of individuals with alcohol dependence Syndrome had significantly higher scores in Family Interaction Pattern Scale; especially in the domains of reinforcement and role as compared to spouses of normal individuals. It also suggested that the level of codependency was significantly higher to the spouses of individuals with Alcohol Dependence Syndrome as compared to spouses of normal individuals.